Morphine administration selectively facilitates social play in common marmosets - Guard, Heather J.; Newman, John D.; Roberts, R. Lucille (Developmental psychobiology, 2002)
Common marmosets (Callithrix jacchus) form extended families, and several cohorts of young may reside together. Play is shown extensively among the offspring. We hypothesized that opiate activity modulates social play, and predicted that administration of morphine (0.5 mg/kg) would facilitate social play, whereas pretreatment with naloxone (0.5 mg/kg) would block morphine's effects. Morphine administration was associated with significantly increased social play, and the effect of morphine was attributable to the focal subject, since play initiated by others was unaffected by treatment. Non‐social categories of play, such as object manipulation and locomotor play, and affiliative behaviors, such as time spent huddled, were unaffected by treatment. Twittering and play face, behaviors used by young during play, also increased after morphine administration. Pretreatment with naloxone blocked morphine's effects. Total activity was significantly increased by morphine administration. We conclude that social play is specifically facilitated by opiate activation, whereas other categories of play behavior and social behavior were unaffected by morphine. Thus, social play represents a distinct category of social behavior in juvenile common marmosets with regulatory processes that are unique from other types of social behavior. Published 2002 Wiley Periodicals, Inc. Dev Psychobiol 41: 37–49, 2002. Published online in Wiley InterScience (www.interscience.wiley.com). DOI 10.1002/dev.10043